Does warning participants attenuate the retrieval-enhanced suggestibility effect? : exploring a retrieval fluency explanation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatū, New Zealand - Naus, Amanda (Massey University, 2014)
The purpose of the current research was to explore a retrieval fluency explanation for the retrieval-enhanced suggestibility (RES) effect and to investigate whether the RES effect can be reduced with a warning. Participants were a volunteer sample of 91 people between 18 and 45 from across New Zealand, recruited via social media and word of mouth. A 3 x 2 x 2 factorial design was used, with participants being assigned to either the single testing or repeated testing condition, and either the warning or no warning condition. Item type (misinformation, consistent, or control) was manipulated within-subjects. Participants watched a video, then either took a 15 question forced-choice test or played the video game Tetris. All participants then read a summary of the video event, which contained some misleading information. Participants in the warning conditions were then warned the information may not be accurate. After watching a distractor video, all participants completed the same 15 question forced-choice test that has been used earlier. Average hit rates, confidence ratings, and response latencies were measured. It was hypothesised that participants in the repeated testing condition would report more of the misinformation and consistent items on the final test, compared to participants in the single testing condition, but only for participants who were not warned. It was also hypothesised that participants in the repeated testing condition would have higher confidence, and faster response latencies, for misinformation and consistent items, than participants in the single testing condition, but only for participants who were not warned. Results showed there was limited evidence for the RES effect, and some evidence for a response.
Keywords: Mental suggestion; Memory; Witnesses; Psychology; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Cognitive science